Education Reduces Recidivism - Magee, Gregory (Technium Social Sciences Journal, 2021)
The research addresses how and why formal education lowers recidivism rates. Formal education means much of the learning comes from a book or other learning material delivered by a trained teacher. The two types of formal education discussed are academic and vocational education. Statistics for lowered recidivism rates resulting from education are essential to support this topic. How education, either academic or vocational, can prevent crime was the first avenue of the research topic that is explored. There are countless opportunities higher education provides to individuals. Next, a direct correlation between education and crime was looked at from a statistical view regarding the recidivism rate. The progress education has on the prison system exposes the results. A simple examination of statistics regarding the recidivism rate of the selected participants involved in the prison education system will resemble what success or effectiveness has come from education being implemented.